Advanced Power MOSFET Concepts - Baliga, B. Jayant (Springer US : Imprint: Springer, 2010)
"Advanced Power MOSFET Concepts" provides an in-depth treatment of the physics of operation of advanced power MOSFETs. Analytical models for explaining the operation of all the advanced power MOSFETs are developed and explained. The results of numerical simulations are provided to give additional insight into the device physics and validate the analytical models. The results of two-dimensional simulations are also given, in order to corroborate the analytical models and give further insight into the device operation. This volume also: -Discusses devices that can have a significant impact on improving the efficiency of the voltage-regulator-modules used to deliver power to microprocessors and graphics chips in laptops and servers -Covers applications in all lower voltage circuits, especially the automotive electronics area Includes numerical simulation examples to explain the operating physics and validate the models - Offers extensive coverage of the role of silicon carbide in the design and structure of power rectifiers "Advanced Power MOSFET Concepts" is a must-read for researchers and practicing engineers in the power device industry.